Republic of the Marshall Islands : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Republic of the Marshall Islands. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that the economy of the Marshall Islands is estimated to have expanded by about 0.5 percent in FY2015 (ending September 30), as the fishery sector recovered. Following a moderate inflation of 1.1 percent in FY2014, headline inflation dropped to -2.2 percent in FY2015 amid falling oil and utility prices. The fiscal balance is estimated to have recorded a surplus of about 3 percent of GDP in FY2014-15, owing to record-high fishing license fees. Growth is expected to rise to about 1.5 percent and inflation to about 0.5 percent in FY2016, as the effects of the drought in earlier 2016 are offset by the resumption of infrastructure projects.